Psychological Empowerment: A systemic model with individual and community components - Banda Castro, Ana Lilia (2015)
This study aimed to confirm that social participation may influence empowerment as one ofthe four components explained by the theory. The hypothesis proposes systemic interaction of two components of empowerment: intrapersonal and behavioral. 113 urban residents participated in the study. The hypotheses were tested through the use of structural modeling. An intrapersonal component of empowerment, composed of positive empowerment, negative empowerment and socio-political control was identified. This component was affected by the behavioral component that involves social organization, community action and decision making. The hypothesis is accepted and the study provides empirical support to the theory.